2010
DOI: 10.1021/ed8001144
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Sequencing Jigsaw

Abstract: The jigsaw technique has been used in a fourth-year biochemistry course to increase problem-solving abilities of the students. The jigsaw method is a cooperative-learning technique that involves a group structure. Students start with a “home” group. That group is responsible for learning an assigned portion of a task. Then the instructor separates students into new groups, the “jigsaw groups”, by assigning one member from each home group to a new group. In the jigsaw group, students share information and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…All the students passed the exam; however, it was observed that the students answered better the questions that included concepts about the topics that had been taught with new learning methods, since the 96.3% of the students answered correctly the questions related to Hydrogen and Energy outlook. This finding agrees with the results obtained by other authors [9].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…All the students passed the exam; however, it was observed that the students answered better the questions that included concepts about the topics that had been taught with new learning methods, since the 96.3% of the students answered correctly the questions related to Hydrogen and Energy outlook. This finding agrees with the results obtained by other authors [9].…”
Section: Resultssupporting
confidence: 94%
“…Some different learning methodologies have been analyzed in a wide range of study cases [8][9][10][11][12][13][14][15][16], with the aim of improving the learning process. However, not all techniques are useful when the number of students is high [17].…”
Section: Introductionmentioning
confidence: 99%
“…The JT has been used in various fields, such as mathematics (Camp Mora et al, 2007;Lluch Peris, 2007), microbiology (Baviskar, 2013;Soto et al, 2011), computer programming (Anguas et al, 2007), physical education (Navarro Leandro et al, 2008), chemistry (Davis-McGibony, 2010;Doymus, 2008) and medicine and nursing (Buhr et al, 2014;Renganathan, 2013), producing positive results in satisfaction and the acquisition of knowledge. The technique has also been shown to increase students' self-efficacy in French language and mathematics courses (Darnon et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Considering its main characteristics, this technique encourages mutual learning among students from the articulation between the activities and the studied contents, so that, even though the work is collective, there is an individual responsibility for a good group performance, which can be accomplished through individual tests and division of roles and contents, among other strategies. Thus, no student will be successful unless all his or her group fellows also are …”
mentioning
confidence: 99%
“…The use of this method has been explored in several areas of chemistry, for example, atomic models, phase diagrams, and protein sequencing …”
mentioning
confidence: 99%